The Dirichlet problem for the Beltrami equations in simply connected domains - Petkov, I. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Under certain conditions on the dilatation coefficient Kµ, the existence of regular solutions of the Dirichlet problem for the Beltrami equations in arbitrary simply connected domains is proved.